A Study on Accounting Software Used by Accountants in Various Organization - Farheen, Ansari Sana; Tidke, Sunita (Nepalese Journal of Management Science and Research, 2025)
This study examines the importance of accounting software in improving financial reporting accuracy and efficiency in businesses. It explores the factors influencing the adoption of accounting software among accountants and evaluates the challenges they face in using it. The research uses a structural equation model to assess factors such as Performance Expectancy, Effort Expectancy, Social Influence, and Perceived Security, which significantly impact behavioral intention. Additionally, the study identifies key challenges, including software bugs, limited customization, complex interfaces, data risks, high licensing costs, poor customer support, and inadequate fraud detection features. The findings highlight the need for effective accounting software to avoid financial losses and support decision-making in an increasingly globalized business environment.